Connective tissue of cervical carcinoma xenografts: Associations with tumor hypoxia and interstitial fluid pressure and its assessment by DCE-MRI and DW-MRI. (January 2014) - Hompland, Tord; Ellingsen, Christine; Galappathi, Kanthi; Rofstad, Einar K.
Abstract Background. A high fraction of stroma in malignant tissues is associated with tumor progression, metastasis, and poor prognosis. Possible correlations between the stromal and physiologic microenvironments of tumors and the potential of dynamic contrast-enhanced (DCE) and diffusion-weighted (DW) magnetic resonance imaging (MRI) in quantification of the stromal microenvironment were investigated in this study. Material and methods. CK-160 cervical carcinoma xenografts were used as preclinical tumor model. A total of 43 tumors were included in the study, and of these tumors, 17 were used to search for correlations between the stromal and physiologic microenvironments, 11 were subjected to DCE-MRI, and 15 were subjected to DW-MRI. DCE-MRI and DW-MRI were carried out at 1.5 T with a clinical MR scanner and a slotted tube resonator transceiver coil constructed for mice. Fraction of connective tissue (CTFCol) and fraction of hypoxic tissue (HFPim) were determined by immunohistochemistry. A Millar SPC 320 catheter was used to measure tumor interstitial fluid pressure (IFP). Results. CTFCol showed a positive correlation to IFP and an inverse correlation to HFPim. The apparent diffusion coefficient assessed by DW-MRI was inversely correlated to CTFCol, whereas no correlation was found between DCE-MRI-derived parameters and CTFCol. Conclusion. DW-MRI is a potentially useful method for characterizing the stromal microenvironment of tumors.